Desain Kelembagaan KPU dalam Siklus Pemilu: Rekonstruksi Kewenangan dan Akuntabilitas Fiskal di Indonesia - Nancy Juni Augusteyn; Saryono Yohanes; Dhey W.Tadeus (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
This article examines the legal design of the General Elections Commission (KPU), the variability of its workload across the electoral cycle, and its implications for fiscal accountability. The study employs normative legal research using statutory, conceptual, historical, and limited comparative approaches. Primary legal materials comprise the 1945 Constitution, electoral legislation, state-finance legislation, and relevant Constitutional Court decisions. The findings demonstrate that positive law does not leave the KPU without functions between formal electoral stages because voter-data maintenance, public education, evaluation, reporting, system management, and institutional preparation continue throughout the cycle. Nevertheless, existing regulations do not adequately distinguish the permanent institutional core, continuous services, and temporary surge functions or connect them with measurable workload, staffing, performance, and budget standards. Accordingly, the central problem concerns legal calibration and accountability rather than a proven normative vacuum or fiscal loss. The study recommends maintaining a permanent and independent KPU while introducing cycle-responsive staffing, budgeting, performance indicators, and periodic functional and fiscal audits. The PPU–UTKN model should remain a long-term constitutional alternative requiring stronger empirical and constitutional justification.